Targeting the initial investigation and management in cases of acute pulmonary embolism. Issue 1 (27th August 2013) - Moore, Nicholas; Hawkins, Peter
Abstract: It was noted by consultants in our hospital that the early investigation of suspected pulmonary embolism (PE) lacked structure. This was causing delays in definitive diagnosis and early management. The resulting unnecessary use of investigation was also wasting resources. In particular, the inappropriate use of serum d-dimer tests was causing concern. The National Institute of Clinical Excellence (NICE) guidelines recommend use of the 2-level Well's score to target investigation in suspected PE. A baseline audit against the NICE guideline revealed that Well's scores were rarely used (only calculated in 12% of cases) and confirmed the suspicion that early investigation was poorly targeted. This project intervened using educational talks promoting the use of Well's scores in cases of suspected PE. Well's score proformas were placed in the emergency department and emergency assessment unit for reference. Their availability was advertised. This significantly increased the use of Well's scores (46% vs 11%, p <0.001). Fewer patients underwent unnecessary d-dimer measurements in cases of likely PE (65% vs 86%). Initial investigation was more targeted in cases where a Well's score had been calculated than in cases without a Well's score. For example, significantly fewer unnecessary d-dimer tests were performed in these cases (45% vs 100%, p < 0.05). The cost of unnecessary investigation in suspected PE is not only significant financially but also in the resulting delay in definitive diagnosis and management for the patient. The simple intervention used here was effective in addressing this problem.